2020
DOI: 10.1159/000504338
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Hemophilia in an Elderly Patient with Carcinoma of the Ampulla of Vater

Abstract: KeywordsAcquired hemophilia · Carcinoma of the ampulla of Vater · Paraneoplastic acquired hemophilia Abstract Acquired hemophilia is a rare autoimmune bleeding disorder related to the production of autoantibodies that inhibit clotting factor VIII or IX. The underlying cause can be autoimmune disease, malignancy, pregnancy, or medications, but it is most commonly idiopathic. Here we present the case of an 81-year-old patient with locoregionally relapsed periampullary carcinoma who presented with soft tissue hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Usually AHA is seen in post operative period as seen in literature review by S. Reitter et al in 4 cases of pancreatic cancer [ 4 ]. Similarly Mavroeidis et al reported AHA in postoperative case carcinoma of ampulla of vater after two month of surgery which was attributed to peritoneal metastatic disease which was also confirmed by Geethakumari et al adenocarcinoma of pancreas [ 10 , 11 ]. None of the cases reported in preoperative period as per our knowledge.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Usually AHA is seen in post operative period as seen in literature review by S. Reitter et al in 4 cases of pancreatic cancer [ 4 ]. Similarly Mavroeidis et al reported AHA in postoperative case carcinoma of ampulla of vater after two month of surgery which was attributed to peritoneal metastatic disease which was also confirmed by Geethakumari et al adenocarcinoma of pancreas [ 10 , 11 ]. None of the cases reported in preoperative period as per our knowledge.…”
Section: Discussionmentioning
confidence: 78%
“…Mavroeidis et al and Geethakumari et al had reported paraneoplastic hemophilia associated with pancreatic cancer [ 10 , 11 ]. We report our experience of another case of paraneoplastic hemophilia associated with periampullary cancer in an elderly patient in preoperative period after thorough investigation and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation